2020
DOI: 10.1007/s13353-020-00548-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of important resident brown trout breeding lines in Poland

Abstract: The history of brown trout Salmo trutta L. stocking has long tradition in the European Union and other countries. Hundreds of hatchery facilities on continent have artificial broodstocks used for enhancement of neighbouring and also geographically far river basins. These practices have substantial effect on wild brown trout populations. To illuminate this phenomenon, eleven hatchery stocks and wild populations from northern Poland and Carpathian region were analysed using 13 microsatellite markers. Obtained re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…The overall F ST was much lower (0.024) when only the free migration area was considered without juveniles from hybridization zones. This level of internal population differentiation was similar to that of neighboring Pomeranian rivers or the Vistula River 42 , 43 and to that in anadromous populations from larger Baltic Sea rivers such as the Umealven, Laisalven, or Luga 44 , 45 . Evidence of genetic differentiation among brown trout populations that are fragmented by barriers are reported by many authors 46 48 ; however, such high differences among neighboring locations in one river are reported less frequently 49 .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The overall F ST was much lower (0.024) when only the free migration area was considered without juveniles from hybridization zones. This level of internal population differentiation was similar to that of neighboring Pomeranian rivers or the Vistula River 42 , 43 and to that in anadromous populations from larger Baltic Sea rivers such as the Umealven, Laisalven, or Luga 44 , 45 . Evidence of genetic differentiation among brown trout populations that are fragmented by barriers are reported by many authors 46 48 ; however, such high differences among neighboring locations in one river are reported less frequently 49 .…”
Section: Discussionsupporting
confidence: 62%
“…An analysis of stocking history in the Parsęta River basin dating to the 1970s showed no evidence of stocking in this part of the basin and especially not upstream of barriers on the Mogilica River. Studies published recently on the genetic diversity of brown trout breeding lineages in Poland indicated that, despite high genetic diversity 43 , this isolated population was clustered together with breeding lineages from northern Poland.…”
Section: Discussionmentioning
confidence: 94%
“…Fertilized sea trout eggs were obtained in late October and early November from fish in the broodstock maintained at the Department of Salmonid Research, Inland Fisheries Institute in Olsztyn (DSR IFI Olsztyn). Among the broodstocks at the DSR IFI Olsztyn is a sea trout broodstock that was built using the Vistula sea trout population (Bernaś and Wąs-Barcz, 2020). All of the tanks in which the fish are kept were supplied with water from the Radunia River (Kashubian Lake District, northern Poland).…”
Section: Fish Originmentioning
confidence: 99%
“…Already established measures such as stocking can, properly applied, stabilise depressed populations. However, long‐term stocking has often been associated with stocking different genetic backgrounds (Aas et al, 2018; Bernaś & Wąs‐Barcz, 2020; Finnegan & Stevens, 2008) and this can lead to negative genetic effects on extant populations when stocked and wild fish interbreed (e.g. Machordom et al, 1999; Nielsen et al, 2001; Marzano et al, 2003; McGinnity et al, 2003; Ferguson, 2006).…”
Section: Implications For Research and Managementmentioning
confidence: 99%
“…Decreasing population trends for Salmo trutta fario are reported from its southern distribution range, for example Spain as vulnerable (Doadrio, 2001) and Andalusia as endangered (Ruíz & Rodríguez de los Santos, 2001), mostly due to climatic change. However, the intense and routine stocking of brown trout practised throughout Europe since the beginning of the 20th Century may potentially be masking the real status of natural populations (Bernaś & Wąs‐Barcz, 2020).…”
Section: Introductionmentioning
confidence: 99%